2000
DOI: 10.1074/jbc.275.4.2607
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lumican in the Corneal Epithelium during Wound Healing

Abstract: Lumican regulates collagenous matrix assembly as a keratan sulfate proteoglycan in the cornea and is also present in the connective tissues of other organs and embryonic corneal stroma as a glycoprotein. In normal unwounded cornea, lumican is expressed by stromal keratocytes. Our data show that injured mouse corneal epithelium ectopically and transiently expresses lumican during the early phase of wound healing, suggesting a potential lumican functionality unrelated to regulation of collagen fibrillogenesis, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
204
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 210 publications
(218 citation statements)
references
References 35 publications
7
204
0
3
Order By: Relevance
“…We know that lumican regulates collagen fibril diameter and organization in the adult cornea (Chakravarti et al, 1998;2000;Saika et al, 2000). The spatial distribution of collagen fibrillar ultrastructural anomalies coincides with the posterior-rich distribution of lumican in the normal cornea, with transparency defects localized to the posterior stroma of the Lum Ϫ/Ϫ cornea.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We know that lumican regulates collagen fibril diameter and organization in the adult cornea (Chakravarti et al, 1998;2000;Saika et al, 2000). The spatial distribution of collagen fibrillar ultrastructural anomalies coincides with the posterior-rich distribution of lumican in the normal cornea, with transparency defects localized to the posterior stroma of the Lum Ϫ/Ϫ cornea.…”
Section: Discussionmentioning
confidence: 68%
“…Earlier structural studies were done using adult lumican knockout mice and demonstrated defects in collagen fibril structure and organization in the adult posterior stroma (Chakravarti et al, 1998Saika et al, 2000). Here, we focused on analyzing the developmental acquisition of this phenotype.…”
Section: Corneal Collagen Fibril Structure During Postnatal Developmementioning
confidence: 99%
See 1 more Smart Citation
“…Some progress has been made, particularly with respect to our understanding of what factors govern corneal fibril size 49,50 and organisation, including the roles of the ambient ions 51 and of proteoglycans. The recent availability of gene-targeted mice with null mutations for selected proteoglycans [52][53][54] now makes it possible to correlate the structural effect of selected deletions with tissue transparency. For example, it is interesting that lumican-null mice have cloudy corneas, 52 decorin-null mice have clear corneas, 53 and keratocan-null mice have mostly clear corneas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is interesting that lumican-null mice have cloudy corneas, 52 decorin-null mice have clear corneas, 53 and keratocan-null mice have mostly clear corneas. 54 These and similar tissues open the possibility to greatly increase our understanding of the causes of light scattering from abnormal corneas in the near future. Figure 11 The Summation of Scattered Fields method was used to predict transmission as a function of wavelength in a rabbit cornea 8 months after PTK and in its control cornea.…”
Section: Discussionmentioning
confidence: 99%